2012
DOI: 10.1371/journal.pone.0037471
|View full text |Cite
|
Sign up to set email alerts
|

Uptake Rate of Cationic Mitochondrial Inhibitor MKT-077 Determines Cellular Oxygen Consumption Change in Carcinoma Cells

Abstract: ObjectiveSince tumor radiation response is oxygen-dependent, radiosensitivity can be enhanced by increasing tumor oxygenation. Theoretically, inhibiting cellular oxygen consumption is the most efficient way to increase oxygen levels. The cationic, rhodacyanine dye-analog MKT-077 inhibits mitochondrial respiration and could be an effective metabolic inhibitor. However, the relationship between cellular MKT-077 uptake and metabolic inhibition is unknown. We hypothesized that rat and human mammary carcinoma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…MKT-077 is selectively accumulated in mitochondria because of its lipophilic cationic property sensitive to Δψ m [ 15 29 ]. The degree of its mitochondrial accumulation therefore can vary among different cell types [ 16 30 ]. To understand why MKT-077 induced differential growth inhibitory effects on TT and MZ-CRC-1 cells, we determined whether MKT-077 was accumulated in these cells at a similar degree.…”
Section: Resultsmentioning
confidence: 99%
“…MKT-077 is selectively accumulated in mitochondria because of its lipophilic cationic property sensitive to Δψ m [ 15 29 ]. The degree of its mitochondrial accumulation therefore can vary among different cell types [ 16 30 ]. To understand why MKT-077 induced differential growth inhibitory effects on TT and MZ-CRC-1 cells, we determined whether MKT-077 was accumulated in these cells at a similar degree.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that the MKT-077 cation, by decreasing the rate of oxygen consumption, may increase tumor oxygen levels and radiosensitivity. 599 …”
Section: Mitochondria-targeted Therapeutics In the Pre-clinical Momentioning
confidence: 99%
“…Furthermore, the method was used to provide a high-resolution map of oxygen levels in and around a hydrogel-embedded 3D cell culture. Computational modeling and curve fitting of the observed oxygen gradient provided cell specific parameters for the oxygen uptake rate, V max and K m 38,39 . The results provide a cautionary note for interchangeable use of different methods to form and culture spheroids, even if the spheroid size and shape appear the same.…”
Section: Discussionmentioning
confidence: 99%
“…Even ratiometric imaging with an oxygen-insensitive reference dye present is challenging, as photo-bleaching properties and excitation/emission properties will be different between the oxygen-sensitive and oxygen-independent dye. In contrast, measurement methods that depend on the indicator’s luminescent lifetime, such as phase fluorimetric measurements 34,38,48 , can usually eliminate inconsistencies that arise from intensity differences, caused by dye-loading variability, photobleaching, and optical path variability inherent to 3D tissues 48,49 . Using small, dispersible polydimethylsiloxane (PDMS)-based oxygen sensing microbeads with phase fluorimetry 18,19 we quantified significant differences in oxygen microenvironments between three different but commonly-used 3D culture formats.…”
Section: Introductionmentioning
confidence: 99%